How do mathematics teachers design tasks to assess students’ creative thinking ability? - Pradnyo Wijayanti; Tatag Yuli Eko Siswono; Dwi Juniati; Abadi Abadi; Sugi Hartono (Jurnal Riset Pendidikan Matematika, 2022)
This study aims to describe teachers' understanding of designing mathematical tasks to assess students' creative thinking abilities. The descriptive study involved 23 mathematics teachers in a city in East Java, Indonesia. The research Instrument is a task that reveals teachers' understanding of the notion of creative thinking, mathematics' problem of assessing students' creative thinking, some criteria to assess students' creative thinking, and examples of questions designed by the teacher. Data were analyzed descriptive-quantitatively and qualitatively with an iterative method consisting of data condensation, data display, and data verification. The study results indicate that teachers' understanding of creative thinking is still lacking, how to assess, and assessment criteria, their abilities still need to be improved